2013
DOI: 10.1002/chem.201303757
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Probes Based on Nucleophilic Substitution–Cyclization for Hydrogen Sulfide Detection and Bioimaging

Abstract: The design, synthesis, properties, and cell imaging applications of a series of pyridine-disulfide based fluorescent probes (WSP1, WSP2, WSP3, WSP4 and WSP5) for hydrogen sulfide detection are reported. The strategy is based on the dual-nucleophilicity of hydrogen sulfide. A hydrogen sulfide mediated tandem nucleophilic substitution-cyclization reaction is used to release the fluorophores and turn on the fluorescence. The probes showed high sensitivity and selectivity for hydrogen sulfide over other reactive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
135
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 209 publications
(138 citation statements)
references
References 50 publications
3
135
0
Order By: Relevance
“…Xian et al reported a fluorescein-based probe, WSP1-5 ( Fig. 3b) [27,28], in which the disulfide bond is cleaved by H2S followed by intramolecular nucleophilic attack of the persulfide group on the ester moiety to release the fluorophore, with a large fluorescence increase. Guo et al reported a reversible fluorescent probe, CouMC (Fig.…”
Section: Fluorescent Probes Based On the Nucleophilicity Of Hs -mentioning
confidence: 98%
“…Xian et al reported a fluorescein-based probe, WSP1-5 ( Fig. 3b) [27,28], in which the disulfide bond is cleaved by H2S followed by intramolecular nucleophilic attack of the persulfide group on the ester moiety to release the fluorophore, with a large fluorescence increase. Guo et al reported a reversible fluorescent probe, CouMC (Fig.…”
Section: Fluorescent Probes Based On the Nucleophilicity Of Hs -mentioning
confidence: 98%
“…Based on the 1:1 binding mode, the association constant (K) was evaluated using the Benesi-Hildebrand method and was found to be 6.4 Â 10 4 M À 1 (Fig. 1b) [19]. The fluorescence intensity changes of FL at 524 nm exhibited a linear correlation to Cu 2 þ in the concentration range from 0 to 0.8 μM (R 2 ¼0.9982) (Fig.…”
Section: Spectroscopic Studies Of Fl In the Presence Of Cu 2 þmentioning
confidence: 99%
“…Exposure to high level of S 2 À can produce various physiological and biochemical problems including irritation in mucous membranes, unconsciousness and respiratory paralysis. Furthermore, the protonated forms HS À or H 2 S are more toxic than the S 2 À itself [19,23,25]. Therefore, a rapid and sensitive method for immediate copper and sulfide monitoring in aqueous media and in biological systems is highly essential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] Therefore, it is of scientific interest to develop selective methods for real time monitoring of H 2 S in living cells, mapping its physiological and pathological consequences. Fluorescence trapping with H 2 S-responsive fluorescent probe offers an attractive molecular imaging technique for the in vivo detection, [14][15][16][17][18][19][20] mostly based on its unique chemical reactivity, such as exploiting selective H 2 S-mediated reduction of azides, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] trapping H 2 S by proximate bis-electrophile centers, [37][38][39][40][41][42][43] and employing copper sulfide precipitation strategies. [44][45] However, trapping endogenous production of H 2 S in living cells is still a challenge due to common problems in sensitivity, selectivity and chemostability/photostability with currently available probes.…”
Section: Introductionmentioning
confidence: 99%